Evaluating the Role of GCC Nations in Sustainable Energy Investment Using an Enhanced Low-Carbon Economy Index - Alsiyabi M.; Hassan H.; Khudari M. (Creative Publishing House, 2025)
In the past decade, environmental, social and country governance (ESG) aspects as well as economy have become key factors for decisions in the investment and future development of renewable energy industry. The abundancy of renewable resources and widely accessible technology are the key drivers for the renewable energy business in the GCC. However, lack of effective policies and regulations, along with subsidized fuel prices, are slowing down the implementation of renewable resource options. This study will i llustrate the potential, the challenges, and the barriers of implementing renewable energy technologies in the GCC region. In addition, this research empirically examines the impact of renewable energy sources and other factors in the GCC countries. This study can be used as a screening tool, decision making tool, benchmarking tool and guidance of sustainable development. ? 2024, Creative Publishing House. All rights reserved.